Idiopathic meconium peritonitis as a surgical emergency: A case report in a newborn - Ana Jimenez Uribe; Armando Rojas Sanchez; Fernando Fierro Avila (Case Reports)
Meconium peritonitis is a rarely described condition that is typically found in fetal and perinatal patients. It manifests in different ways and requires an early diagnosis. In this case report, a clinical suspicion of the disease was made at the antenatal period through an obstetric ultrasound scan showing an abdominal mass in both the bottom and top right quadrants. The patient initial symptoms were those of acute intestinal obstruction. Nevertheless, these symptoms improved after surgical approach was timely performed. Based on this outcome, it can be concluded that a favorable outcome to this pathology depends on its early diagnosis, since an early diagnosis decreases morbidity and mortality chances.